Evaluation of eHealth deployment at primary care in the EU member states by usage of selected MCDM methods - Eva Ardielli (Review of Economic Perspectives, 2020)
Information and Communication Technologies have become a revolutionary part of European healthcare in recent years. The European Commission considers eHealth as an important and appropriate tool that can contribute to cope with the challenges that are currently affecting the healthcare systems in Europe. The development of eHealth is therefore embedded in many EU strategies and is being evaluated on an ongoing basis. In the past, several studies have been carried out focusing on the evaluation of individual areas of eHealth - especially on the area of primary care secured by General Practitioners and Acute Hospitals. However, no synthesis of these works was made. This paper is focused on the proposing of an assessment for both mentioned areas of eHealth. The aim is to evaluate the eHealth deployment in the European Union Member States by the synthesis of Composite Indicators in existing studies into the evaluation model based on the application of Multiple-Criteria Decision-Making techniques. The evaluation is performed by the usage of TOPSIS, WSA, and MAPPAC method. The result of the research is the design of an evaluation framework for eHealth that enables the comparison of eHealth indicators in the international context and evaluation of eHealth deployment in European Union Member States in the form of a ranking. In this ranking, the Nordic countries are among the best-rated countries, while the worst-rated countries are in Eastern Europe.
Keywords: C38; H11; I11; 330; eHealth; European Union; EU countries; Evaluation; MCDM